Pengaruh Kapasitas Penyerapan terhadap Kinerja UMKM dengan Kelincahan Pemasaran sebagai Variabel Mediasi - Bili, Sarinda A.; Situmorang, Tumpal Pangihutan; Pakereng, Yulita Mila (Jurnal Ilmiah Global Education, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in strengthening a sustainable economy, with their ability to adapt to market changes and create products or services that meet local and global needs. MSMEs contribute significantly to job creation and inclusive economic growth. The performance and sustainability of MSMEs are influenced by internal and external factors, including absorption capacity and marketing agility. Absorption capacity refers to the ability of MSMEs to absorb, manage, and apply new knowledge to improve competitiveness and performance. Marketing agility serves as a mediator that ensures the knowledge absorbed can be applied to improve business performance. This study aims to examine the influence of absorption capacity on the performance of MSMEs with marketing agility as a mediating variable. The research method used is quantitative with a primary research approach. Data was collected through a questionnaire distributed to 200 MSME actors in Waingapu City District. Data analysis uses Partial Least Squares (PLS) to test the influence between absorption capacity, marketing agility, and MSME performance. The results of the study show that absorption capacity has a positive effect on the performance of MSMEs, both directly and through marketing agility as a mediator. These findings contribute to the understanding of the factors that drive the improvement of MSME performance, as well as the importance of adaptability to market changes in increasing the competitiveness of MSMEs.